Preliminary analysis of biomass potentially useful for producing biodiesel (2011)
Given that biodiesel is emerging as a viable solution for some energy and environmental problems, research on raw materials appropriate for its production is a matter of growing interest. In this study we present the results of research devoted to preliminary analysis on several vegetable (biomass) species potentially useful for producing biodiesel. The bioprospection zone is a region on the Colombian Pacific coast. The candidate species collected underwent different standardized ASTM tests in order for us to define properties that facilitate their evaluation. Some of the species underwent a transesterification process. Comparisons between the thermo-physical properties of the biofuels obtained and the properties of commercial diesel were carried out. Also, performance tests for these biofuels were conducted in compression ignition engines, particularly evaluating efficiency, fuel consumption, and potency at different RPMs.